INFLUENCIA DE LA PRECIPITACIÓN SOBRE LA CONCENTRACIÓN DEL RADÓN EN EL SUELO: SIMULACIÓN EN LABORATORIO Y COMPARACIÓN CON DATOS DE CAMPO - García-Vindas, J. R. (2011)
This paper presents the most relevant results of laboratory experiences and its comparison tofield data. Their objective is to better understand the precipitation effect on the radon gas emanations. The results obtained in the laboratory and the predictions of the model suggested are in completely concordance withfield data. It is useful as a filter source for further data.